Thirty years of satellite derived bathymetry – The charting tool that hydrographers can no longer ignore - Laporte, Jean; Dolou, Henri; Avis, Joseph; Arino, Olivier (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 2020 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Laporte, J., Dolou, H., Avis, J., and Arino, O. (2000). Thirty years of satellite derived bathymetry – The charting tool that hydrographers can no longer ignore. The International Hydrographic Review, 24, 129–154. https://ihr.iho.int/articles/thirty-years-of-satellite-derived-bathymetry-the-charting-tool-thathydrographers-can-no-longer-ignore/ Thirty years after being introduced into national chart series, Satellite Derived Bathymetry (SDB) charts are still struggling to be recognised as valid navigation documents, capable of meeting the level of confidence required by the S-44 IHO standards for hydrographic surveys. The advent of new generation satellite constellations, such as Sentinel-2*, provide improved geolocation and, thanks to higher revisit frequency, an almost unlimited capacity to detect natural dangers visible from space within the limits of the sensing instruments. Thus, this negative vision of SDB must change. Written by Hydrographers, this article aims to provide a scientific background adapted to practical Hydrography; introduce the notion of “Perfect Image”, first mentioned at the International Hydrographic Remote Sensing workshop (Ottawa, September 2018); and rehabilitate older concepts such as Depth of Penetration (DOP), which make SDB an incomparable instrument to chart the World’s shallow waters (Fig. 1). Here, “incomparable” does not mean “perfect”, as there are limits to SDB capacity to detect and quantify bottom structures that will be detailed later. *The frequent mention of Sentinel-2 should not lead the reader to believe that the authors are focussing on this constellation. The intention is to show how satellite hydrography has evolved naturally from exploiting unique images to processing large collections that provide ever-improved information, the latest example happening to be Sentinel-2.